Usability within the digital battlefield : usability issues as applied to the digitised battlefield within a Southern African military context - De Jager, Madia (Madia Martie) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MComm)--University of Stellenbosch, 2002.